Smart saline level monitoring system using IOT - Naga Malleswari, B; Vijay varma, P; N.Venkataram, Dr (International Journal of Engineering and Technology, 2018)
This paper relates with the saline level of a patient through remote technology in health care centers to monitor patient’s data constantly. If the patient is sick firstly we should give a saline to patient. When the bottle is placed to patient we should check frequently the level of bottle. It is difficult to check all the time, so we transmit data through thing speak cloud platform to nurse cabin. We can receive the data by indication of bottle level. While setting a tilt sensor near the patient, we may know the patient is in conditional stage or in any Unconditional stage. The system will continuously monitors the patient’s data by this doctor can also monitor many patients at a time.